A Review of the Test of English as a Foreign Language (TOEFL) - Sounkalo, Jiddou (حوليات كلية الآداب والعلوم الإنسانية, 1995)
The article reviews the Test of English as a Foreign Language (TOEFL) for students and prospective teachers of English. It explains the test’s purpose, institutional administration, format, principal sections, timing, and international use. Drawing on the author’s experience as a test taker and teacher, it assesses the relevance of the examination as a measure of English proficiency and as a model for constructing language tests, while drawing attention to aspects that require critical evaluation.